2020
DOI: 10.4162/nrp.2020.14.5.501
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary sodium intake and disease burden and mortality in Koreans between 1998 and 2016: The Korea National Health and Nutrition Examination Survey

Abstract: BACKGROUND/OBJECTIVES: Sodium intake is positively associated with blood pressure, which may increase the risk for cardiovascular disease (CVD). Therefore, we assessed the disease burden of CVD attributable to sodium intakes above 2,000 mg/day and prospectively investigated the association between dietary/urinary sodium levels and the risk of all-cause and CVD-mortality using the Korea National Health and Nutrition Examination Survey (KNHNES). SUBJECTS/METHODS: A total of 68,578 and 33,113 participants were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, since these studies were based on the data collected prior to 1998, it is necessary to understand the latest changes in the diet. While there are other previous studies [ 10 , 11 ] that analyzed more recent data, it remains difficult to understand the changes in the overall nutritional status, as their results are mainly concerned with particular aspects of nutrients, such as energy and sodium.…”
Section: Introductionmentioning
confidence: 99%
“…However, since these studies were based on the data collected prior to 1998, it is necessary to understand the latest changes in the diet. While there are other previous studies [ 10 , 11 ] that analyzed more recent data, it remains difficult to understand the changes in the overall nutritional status, as their results are mainly concerned with particular aspects of nutrients, such as energy and sodium.…”
Section: Introductionmentioning
confidence: 99%
“… 42 Another recently published study using the KNHANES data noted a higher risk of CVD-associated mortality in women with top-quartile sodium intake (energy-adjusted sodium intake >5625 mg/day). 43 In the subgroup analyses, only the coronary artery disease group showed the same results. Hence, our results for MACE may be mainly attributable to those with coronary artery disease.…”
Section: Discussionmentioning
confidence: 67%
“…25 Consistent with our findings, a previous study reported a reduction in sodium intake from 5550 mg/d in 2001 to 3647 mg/d in 2016. 26 Despite this achievement, sodium intake remains above the level recommend by the World Health Organization (<2000 mg/d); thus, continuous actions are needed for further reduction. In the present study, we also observed some unfavorable changes in diet, particularly decreased intake of vegetables and increased intake of sweets and beverages, suggesting that there are remaining targets for dietary improvement in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Responding to high sodium intake reported since 1990, the Korean government has implemented an increasing number of sodium reduction policies that encouraged the food industry to voluntarily reformulate their products and required packaged foods to carry nutrition labels with the information on sodium content . Consistent with our findings, a previous study reported a reduction in sodium intake from 5550 mg/d in 2001 to 3647 mg/d in 2016 . Despite this achievement, sodium intake remains above the level recommend by the World Health Organization (<2000 mg/d); thus, continuous actions are needed for further reduction.…”
Section: Discussionmentioning
confidence: 99%